The Impact of GLP-1 Agonists on Depression Treatment: A Literature Review - Paulina Lemieszek; Katarzyna Rudnicka; Ilona Sajkiewicz; Nadia Miga-Orczykowska; Ilona Jasiuk; Justyna Wójtowicz; Martyna Pustelniak; Katarzyna Krukar; Ewa Łukaszewska; Klaudia Kister; Kamil Chrościński; Jakub Laskowski (Kazimierz Wielki University, 2024)
Introduction Depression is increasingly recognized as a major global health issue, driven by neurobiological, genetic, and environmental factors. Despite extensive research, understanding depression remains challenging due to its complexity and the lack of biomarkers. Recent studies highlight a link between depression and metabolic disturbances, emphasizing the need for alternative therapeutic approaches. Purpose This review aims to explore the therapeutic potential of GLP-1 (glucagon-like peptide-1) in treating depression, focusing on its impact on neurogenesis, neuroinflammation, neurotransmitter imbalances, and synaptic dysfunction. Materials and Methods A systematic review was conducted by analyzing literature from databases such as PubMed and Google Scholar, covering studies from 2003 to 2024. The review focused on keywords related to GLP-1, depression, and diabetes. Description of the State of Knowledge This section discusses the neurobiological mechanisms of depression, including neuroinflammation, neurotransmitter imbalances, and impaired neurogenesis. It highlights the potential of GLP-1 agonists to address these issues and improve mood and cognitive function. Conclusion The review concludes that GLP-1 holds promise as a therapeutic target for depression. Beyond its metabolic roles, GLP-1 can influence brain regions involved in mood regulation, enhance neurogenesis, reduce neuroinflammation, and improve neurotransmitter balance. These effects suggest that GLP-1-based therapies could offer new treatment options for depression, potentially improving outcomes beyond traditional antidepressants.